2013
DOI: 10.1016/j.eats.2013.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Hip Arthroscopic Management for Femoral Head Fractures and Posterior Acetabular Wall Fractures (Pipkin Type IV)

Abstract: Femoral head fractures associated with acetabular fractures are usually treated by an open method. After a closed reduction of a hip dislocation, open reduction and internal fixation of acetabular fractures usually depend on the type of acetabular fracture. Acetabular fractures associated with femoral head fractures, torn labrums, or osteochondral fractures are often managed simultaneously by a posterior approach. The patient in this study was referred to us because of pain and limited motion after open reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 10 publications
0
18
0
1
Order By: Relevance
“…Because the hip is a constrained joint, hip dislocation most commonly occurs following a high‐energy injury. In the general population, hip dislocation is commonly associated with acetabular and femoral head fractures 4,14 . Hsu et al 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Because the hip is a constrained joint, hip dislocation most commonly occurs following a high‐energy injury. In the general population, hip dislocation is commonly associated with acetabular and femoral head fractures 4,14 . Hsu et al 5 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the often-diagnosed fracture of the acetabulum, post-traumatic posterior hip dislocation is frequently accompanied by numerous intra-articular injuries: rupture of the articular capsule, damage to the labrum, rupture of LT, fractures in the femoral head area [ 1 , 2 ]. Each of these intra-articular structures plays significant role in stabilizing the hip joint.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators agree that hip arthroscopy is useful in treating the intra-articular lesions (namely, loose bodies, labral tears, chondral lesions) documented in radiological exams after traumatic hip dislocation in order to prevent further complications. 11 , 12 , 13 , 14 Some (Mullis and Dahners) go further to say that a routine hip arthroscopy should be done after traumatic hip dislocation, as intraoperative loose bodies can be found in patients in which standard radiographic studies found no loose bodies and a concentric reduction was obtained. 15 , 16 …”
Section: Discussionmentioning
confidence: 99%